Social Networks as a Means of Monitoring Students’ Progress - Leonidovna Krivova, Anna (2021)
In the era of the digital educational environment, where each participant of the educational process is actively involved in its development, the Internet and its services have become a popular tool. Open education network tools are defined as ICT tools that ensure the formation and maintenance of network electronic information resources of an open education environment, the implementation of design technologies, and the use of open pedagogical systems. The article aims to reveal methods of monitoring and analyzing students’ learning achievements in higher education institutions using social networks. The main research method was a survey. The article justifies the purposefulness and efficiency of the use of social networks in the process of monitoring and analyzing students’ progress for new learning achievements. The study concludes that the use of social networks for monitoring and analyzing students’ progress ensures the individualization of the learning process and increases the effectiveness of monitoring learning achievements.